2012
DOI: 10.1088/1367-2630/14/3/035009
|View full text |Cite
|
Sign up to set email alerts
|

Melting artificial spin ice

Abstract: Artificial spin ice arrays of micromagnetic islands are a means of engineering additional energy scales and frustration into magnetic materials. Here we demonstrate a magnetic phase transition in an artificial square spin ice and use the symmetry of the lattice to verify the presence of excitations far below the ordering temperature. We do this by measuring the temperature-dependent magnetization in different principal directions and comparing it with simulations of idealized statistical mechanical models. Our… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
126
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(126 citation statements)
references
References 37 publications
0
126
0
Order By: Relevance
“…20 Our use of a spatially resolving imaging method means that we are able to see exactly how the array begins to 'melt' and track the different vertex populations as this happens.…”
Section: Thermal Behaviour Using Field-modified Barrier Heightmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Our use of a spatially resolving imaging method means that we are able to see exactly how the array begins to 'melt' and track the different vertex populations as this happens.…”
Section: Thermal Behaviour Using Field-modified Barrier Heightmentioning
confidence: 99%
“…19 The macrospin ice system has been shown to melt if it is heated close to the Curie point of the underlying microspin system. 20 Developing this concept, it has also been shown that it is possible to repeatedly thermalise an ASI system by using high temperatures to heat the sample in order to access dynamics, cool, then image the arrested state. 21,22 Nevertheless, it is desirable to see the dynamics as they happen in real time.…”
mentioning
confidence: 99%
“…Most of the experimental studies on artificial spin ice have been performed on static systems [3][4][5] or systems with slow magnetization dynamics 6 using imaging techniques such as magnetic force microscopy (MFM) and X-ray photoemission electron microscopy (PEEM). In recent years, however, thermally active artificial spin systems have gained a considerable interest 7 and provided a successful route to reach the low-energy magnetic states of artificial spin ice. 6,[8][9][10][11] Additionally, analysis of the thermal behavior of nanomagnetic systems is particularly important for understanding the limitations of future spintronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a new experimental approach has been devised that seeks thermal activation in these physical simulators by heating close to the Curie temperature (T C ) of the constituent materials [17][18][19][20][21][22][23][24][25]. In this technique, the lithographically-patterned single-domain nanoscale bar magnets that comprise the structure may begin to exhibit spontaneous reversal, driven simultaneously by thermal effects and by the local magnetic environment.…”
mentioning
confidence: 99%